Role of Shariah Supervisory Boards (SSBs) in Islamic Financial Engineering: A Critical Review: A Critical Review - Sheikh, Rafiullah; Hussain, Khalid (Islamic Banking and Finance Review, 2022)
This paper aims to review critically the role of SSBs in Islamic financial engineering. In addition, this paper tries to explore different similarities between SSBs’ and BODs’ roles. It has been found, on the basis of content analysis, that the different roles of a SSB, such as a legislator, consultant/advisor, and auditor, are pivotal in Islamic financial engineering for improving the efficiency of Islamic financial markets. Moreover, different similarities in the roles of SSBs and BODs have been found but to a narrower extent, since SSBs monitor and control the religious side of IFIs. This paper proposes, to incorporate SSBs within the CG structure of two-tier boards, that SSB might be considered as the supervisory board, whereas, the regular BOD needs to be considered as the management board.